Ethanolic Extract of Melia Fructus Has Anti-influenza A Virus Activity by Affecting Viral Entry and Viral RNA Polymerase - Jin, Young-Hee; Choi, Jang-Gi; Cho, Won-Kyung; Ma, Jin Yeul (Frontiers in Microbiology, 2017)
Meliae Fructus (MF) is the dried ripe fruit of Melia toosendan Siebold et Zuccarini, Meliaceae family. MF is widely used in traditional medicine to treat inflammation and helminthic infection and has anti-bacterial, anti-oxidant, anti-cancer, anti-inflammatory, and analgesic activities. However, potential anti-influenza properties of MF have yet to be investigated. We determined whether an ethanolic extract of MF (EMF) has anti-viral activity via an EMF pre-, co-, and post-treatment assay, using the Influenza A/PR/8/34 and H3N2 virus on Madin-Darby canine kidney (MDCK) cells. The EMF had anti-influenza virus activity in pre- and co-treated cells in a dose-dependent manner, but not in post-treated cell. EMF inhibited the activity of hemagglutinin (HA) and neuraminidase (NA) of influenza virus. EMF inhibited viral HA, nucleoprotein (NP), matrix protein 2 (M2), non-structural protein 1 (NS1), polymerase acidic protein (PA), polymerase basic protein 1 (PB1), and polymerase basic protein 2 (PB2) mRNA synthesis at 5 h post infection (hpi), however, the levels of PA, PB1, and PB2 mRNA were increased in pre- and co-EMF treated cells compared with control virus-infected and EMF post-treated cells at 18 hpi. The level of M2 protein expression was also decreased upon pre- and co-treatment with EMF. The PA protein was accumulated and localized in not only the nucleus but also the cytoplasm of virus-infected MDCK cells at 18 hpi. Pre-EMF treatment inhibited the expression of pAKT, which is induced by influenza virus infection, at the stage of virus entry. We also found that treatment of EMF up-regulated the antiviral protein Mx1, which may play a partial role in inhibiting influenza virus infection in pre- and co-EMF treated MDCK cells. In summary, these results strongly suggested that an ethanolic extract of Meliae Fructus inhibited influenza A virus infection by affecting viral entry, PA proteins of the RNA polymerase complex, and Mx1 induction and may be a potential and novel anti-influenza agent.